Blumensaat Line as a Prediction of Native Anterior Cruciate Ligament Length. Issue 8 (6th August 2020) - Joyner, Patrick W.; Mills, Frederic Baker; Brotherton, Scott; Bruce, Jeremy; Roth, Travis; Hess, Ryan; Wilcox, C. Luke; Leddon, Charles E.; Davis, Benjamin; O'Grady, Christopher; Andrews, James R.; Roth, Charles A.
Background: Graft-tunnel mismatch (GTM) is a condition in which the anterior cruciate ligament (ACL) graft is either too long or too short. GTM is particularly problematic when bone–patellar tendon–bone grafts are used because of a potential compromise in fixation of the bone plug on the tibia. Hypothesis: The Blumensaat line (BL), a radiographic landmark representing the roof of the intercondylar fossa, will accurately approximate the native ACL (nACL) length and may aid in the prevention of GTM. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: A total of 130 patients (66 males, 64 females) underwent direct measurement of the nACL during knee arthroscopy. The lengths of the nACL and patellar ligament (PL) were measured intraoperatively, and BL length was measured on lateral knee radiographs. The nACL length was compared with PL and BL lengths to calculate the absolute difference (AD). Mean AD was calculated and used to determine mean percentage difference (MPD). Pearson correlation coefficients (CC) between BL, PL, and nACL length were calculated, along with inter- and intraobserver reliability coefficients for the measurement of BL. Results: For male patients, the mean length of the nACL was 32.5 mm, BL was 30.4 mm, and PL was 49.2 mm. The AD between the BL and nACL was 2.4 ± 1.3 mm, MPD was 2.6% ± 1.9%, and CC was 0.88. The CC between the PL and nACL was 0.08. For female patients, the mean length of the nACL was 30.2 mm, BL was 27.5 mm, and PL was 44.4 mm. The AD between the BL and nACL was 2.7 ± 1.7 mm, MPD was 4.5% ± 2.4%, and CC was 0.93. The CC between the PL and nACL was 0.1. The inter- and intraobserver reliability coefficients for the measurement of BL were 0.86 and 0.83, respectively. Conclusion: A strong correlation was found between BL and nACL with a high inter- and intraobserver reliability. This correlation provides a simple and reliable method to closely approximate nACL length before reconstruction and may aid in the prevention of graft-tunnel mismatch.